Breaches in Infection Prevention and Controls Discovered During an Outbreak Investigation of Two Unlinked Cases of Pseudomonas aeruginosa Bloodstream Infections in a Cardiovascular Thoracic Surgery Unit - Chaiwarith, Romanee; Nunngam, Nantana; Goonna, Aree; Khamnoi, Phadungkiat; Katechanok, Sadubporn; Thana, Umpaipan; Phrommintikul, Arintaya (Biomedical Sciences and Clinical Medicine, 2024)
Two patients with Pseudomonas aeruginosa bloodstream infections were diagnosed a week apart in a cardiovascular thoracic (CVT) surgery unit where there had been no cases of P. aeruginosa infections in the preceding 6 months. An outbreak investigation was conducted. Medical records were reviewed to identify potential common exposure in both patients. Outbreak investigation procedures included cultures of intravenous infusions and various solutions in the operating theatre and the general CVT surgery unit, the intensive care unit and the intermediate care unit, and monitoring compliance with the central line associated bloodstream infection prevention bundle. Both the blood cultures of the two patients as well as the liquid soap used for hand washing in the unit grew P. aeruginosa. However, there were three clonalities of isolates, the first from patient A, the second from patient B, and the third from the liquid soap. Other intravenous infusions and various solutions, i.e., normal saline solution, lactate ringer solutions, solutions for cardiopulmonary bypass circuits, and skin antisepsis, did not grow potential pathogens. In conclusion, although these were unlinked cases, investigation of the cases uncovered breaches in infection control practices and provided an opportunity to improve the infection control strategies in our institution..